Избранные произведения: Пер. с исп. / Габриэль Гарсиа Маркес - Гарсиа Маркес Габриэль (Радуга, 1989)
Экземпляры: РБ (20191225☮) / Инвентарный номер: 19747 / Цена: 03.10 / Авт.знак: Г21 / ББК: 84(7Кол)